Perancangan Strategi Pengembangan Desa Koja Doi sebagai Desa Wisata Berbasis Pariwisata Berkelanjutan di Provinsi Nusa Tenggara Timur - Angelita Peridibua Mudamakin; I Ketut Surata; I Wayan Sukma Winarya Prabawa (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study examines the development strategy of Koja Doi Tourism Village in Sikka Regency as a sustainable tourism destination. The village has strong potential in marine tourism, local culture, and community participation, yet it still faces various challenges in its development. This study aims to identify internal and external conditions, formulate a grand strategy along with alternative strategies, and determine strategic priorities based on sustainable tourism principles. The research employed a mixed-method approach through observation, interviews, documentation, and questionnaires. Data were analyzed using SWOT analysis to identify strengths, weaknesses, opportunities, and threats, while the Analytic Hierarchy Process (AHP) was applied to determine strategic priorities. The results show that Koja Doi Tourism Village has strengths in its marine potential, local culture, and community support, while its main weaknesses lie in accessibility, human resource quality, and limited promotion. The proposed development strategy is directed toward a community-based marine ecotourism model supported by digitalization, strengthening maritime identity, low-emission tourism village development, and wellness marine tourism. The main strategic priority is the development of community-based marine ecotourism. This study concludes that stakeholder synergy through a pentahelix approach is a key factor in realizing Koja Doi Tourism Village as a competitive sustainable tourism destination.